An instrument for measuring health-related quality of life in patients with Deep Venous Thrombosis (DVT): development and validation of Deep Venous Thrombosis Quality of Life (DVTQOL) questionnaire - Stigendal Lennart; Kulich Károly R; Carlsson Jonas; Hedner Ewa; Ingelgård Anders; Wiklund Ingela (Health and Quality of Life Outcomes, 2004)
Abstract Background Few studies have evaluated patient-reported outcomes in connection with a primary event of deep venous thrombosis, partly due to a lack of disease-specific measures. The aim here was to develop a disease-specific health-related quality of life (HRQL) measure, the deep venous thrombosis quality of life questionnaire (DVTQOL), for patients with recent exposition and treatment of proximal deep venous thrombosis. Methods A total of 121 consecutive outpatients (50 % males; mean age 61.2 ± 14 years) treated with warfarin (Waran®) for symptomatic proximal deep venous thrombosis were included in the study. Patients completed the SF-36, EQ-5D and the pilot version of the DVTQOL. Results Items having: high ceiling and floor effect, items with lower factor loadings than 0.50 and items loading in several factors were removed from the pilot version of DVTQOL. In addition, overlapping and redundant items identified by the Rasch analysis were excluded. The final DVTQOL questionnaire consists of 29 items composing six dimensions depicting problems with: emotional distress; symptoms (e.g. pain, swollen ankles, cramp, bruising); limitation in physical activity; hassle with coagulation monitoring; sleep disturbance; and dietary problems. The internal consistency reliability was high (alpha value ranged from 0.79 to 0.93). The relevant domains of the SF-36 and EQ-5D significantly correlated with DVTQOL, thereby confirming its construct validity. Conclusions The DVTQOL is a short and user-friendly instrument with good reliability and validity. Its test-retest reliability and responsiveness to change in clinical trials, however, must be explored.